STRATEGI PEMBINAAN NARAPIDANA RESIDIVIS PENCURIAN DALAM MENCEGAH RESIDIVISME DI LEMBAGA PEMASYARAKATAN KELAS IIA SIDOARJO - Ananda Maulana Singgih Putra; Hartoyo Hartoyo; Subekti Subekti (Universitas Labuhanbatu, 2025)
The Correctional System represents a rehabilitative paradigm in criminal justice that views imprisonment not merely as a punitive measure but as a process of social reintegration grounded in the values of Pancasila, as stipulated in Article 1 paragraph (2) of Law Number 12 of 1995. Nevertheless, the persistence of recidivism, particularly in theft-related offenses, indicates ongoing challenges in the effectiveness of inmate rehabilitation. This study aims to analyze the factors contributing to repeat theft offenses and to evaluate the effectiveness of rehabilitation programs implemented at the Class IIA Correctional Institution in Sidoarjo. The research employs a juridical-empirical approach, with data collected through interviews, observation, and document analysis. Qualitative and systematic analysis reveals that recidivism is influenced by a combination of individual, social, economic, educational, and law enforcement factors. The findings further demonstrate that the Class IIA Sidoarjo Correctional Institution has implemented rehabilitation programs with a relatively high level of effectiveness, particularly through personality development programs that enhance inmates’ self-awareness and vocational training programs that promote independence through work skills. These programs are consistent with the theory of legal effectiveness, encompassing normative implementation, the role of law enforcement officials, and the availability of supporting facilities. Overall, this study highlights the importance of strengthening adaptive and sustainable rehabilitation programs as a strategic approach to preventing recidivism and improving the success of inmates’ social reintegration.Keywords: Recidivism; Theft Offenses; Correctional System; Inmate Rehabilitation